ALIH AKSARA DAN ALIH BAHASA NASKAH/TEKS URAIAN PEPATAH ADAT ELOK NAGARI DEK PANGHULU OLEH DATUK PALITO - Anwar, Fauzi; Nurizzati, Nurizzati; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This article was written to: (a) present a description of the manuscript ofUraian Pepatah Adat Nagari Dek Panghulu oleh Datuk Palito, (b) presents the text of the script interpretation of Uraian Pepatah Adat Elok Nagari Dek Panghulu oleh Datuk Palito, and (c) presents the text of Pepatah Adat Elok Nagari Dek Panghulu oleh Datuk Palito. This research is a philology research. The object of this research is Uraian Pepatah Adat Elok Nagari Dek Panghulu oleh Datuk Palito text. The research method used is descriptive method and the method of philological research that is adapted to the research stages. At the data collection stage used field study and literature study. The results of this research are (1) a complete description of the manuscript, (2) the transcription of literature that can be read and understood by contemporary society about the importance of the role of the penghulu in Minangkabau and the qualities that must be possessed by a penghulu, (3) text that has been adapted to Indonesian Spelling (EBI). In the text of the Description of Adat Elok Nagari Dek Panghulu by Datuk Palito it is found a variety of old Malay and some Minangkabau language vocabulary that is maintained to keep the purity of the vocabulary.Keywords: change of script, transfer of language, text, philology